STUDY OF FACTORS ASSOCIATED WITH THE NUTRITIONAL STATUS OF GRADE 4-6 SDS ANAK BANGSA CERDAS PASURUAN - Ramadivan Bagus Ramadhan; Cleonara Yanuar Dini (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
The problem of child nutritional status is still a health problem in the world as well as in Indonesia. This study aims to determine the relationship between factors related to the nutritional status of elementary school-aged children in grades 4-6 at SDS Anak Bangsa Cerdas Pasuruan. This research is a quantitative research by cross-sectional design which was conducted on 68 pairs of mothers and students in grades 4-6 at SDS Anak Bangsa Cerdas Pasuruan. The results of this study showed that most of the child respondents had moderate levels of physical activity, adequate energy intake, normal nutritional status, and only 41% of mother respondents had the right perception of their child's nutritional status. From the results of the relationship test, it was found that there was a relationship between the level of physical activity (p= 0,002), mother's perception of child's nutritional status (p=0,018), energy intake (p= 0,011) with the nutritional status of children in grades 4-6 SDS Anak Bangsa Cerdas Pasuruan. Researchers suggest for further research to add other independent variables that can relate to the nutritional status of elementary school children.